Relación entre el ingreso y el nivel educativo de los trabajadores en el departamento de Loreto, 2012 – 2021 - Alvarado Vega, Anwar Kelly (2023)
The educational level of the worker is very important, since it represents his human capital which will allow him to access a suitable job, for which the research aims to analyze the relationship between income and the educational level of workers in the Department of Loreto, 2012 - 2021. Likewise, the research is of a descriptive correlational type and of a non-experimental design that counts as the study population the EAP employed in Loreto in the ages 2012 -2021. The investigation concluded that the higher educational level is the one that generates the highest income for workers and the coefficient of the education variable is equal to 140.61, which indicates that as one year of education increases, income is expected to increase in S/. 146.61 soles. Likewise, the value of the determination coefficient R2=0.1435 was determined, which indicates that education does not determine income and there are other factors that better explain the income of workers, in the same way, the correlation coefficient R= 0.3788 was found, which indicates the existence of a weak positive relationship between the variables, that is, the higher the educational level, the higher the income.